World Economic and Financial Surveys : International Capital Markets 1991. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1991)
This paper presents the annual survey of international capital market developments and prospects. It summarizes recent developments in capital market flows and asset prices, including the initial impact of the Middle East crisis, and reviews the main ongoing structural changes in financial markets. A sharp fall in net investment in foreign securities by Japanese institutions in 1990, in the face of narrowing interest rate differentials and, in some cases, the need to cover losses stemming from the fall in the Japanese stock market. In contrast, the importance of net direct investment outflows as a counterpart to the current account surplus began increasing as from 1989. The crisis in the Middle East resulted in a further tightening of market conditions, especially for less creditworthy borrowers. A general preference for safer and more liquid financial instruments was reflected in increased spreads between corporate and government securities on national markets and between private sector Eurobonds and government securities denominated in the same currency on international markets.